The Philosophy of Nature of Ibrahim bin Sayyar Alnazzam - محمد منيرة; السليمان لطيفه (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research aims , through the views of Alnazzam , to present one of the most important philosophical and faith issues and questions that occupied the attention of the Sheikhs of Mu’tazila speakers and their senior scholars : the issue of naturalisms and the questions it raises , and the great existential knowledge it raises in the worldview and the interpretation of its emergence. In addition to the real sources through which to build a vision in this regard . In talking about the movement and the opinion with tranquility and partially and in revealing what is the infinite division . And in the associated visions , perceptions and ideas that were necessary for him to reveal his statement in the boom , and in the negation of the part that is indivisible between them in particular . And about the places of his uniqueness and originality of his views in that and about his rationalistic combining inclination for his cognitive tools and how he deals with nature’s issues , researches the problems of its thorny conceptual field and highlights the apparent ones and what was hidden or what was silent about it. In sum and according to this , the following question is raised : was Alnazzam able to create a philosophy of his own in nature that reveals the extent of the cognitive anxiety that occupied the Arab and Islamic minds at the time and did this subject have a special attention of his scholars , jurists and thinkers . Are there overlaps , discrepancies , or additions between his views in this regard and the opinions of others , whether they are speakers or philosophers , or did reach to a level more than imitation or reference and remain within the general context of the views of Mu’tazila and religious theologians ,? We depend in our attempt to consider that on the analytical method , as well as the comparative method , following the footsteps of any of them , as the nature of the research scientific material and its necessities require considering the opinions it entails.